DEVELOPMENT OF AN INTERVENTION TO IMPROVE COMMUNICATION WITH PEOPLE WITH DEMENTIA IN NURSING HOMES - Machiels, M. (Innov Aging, 2017)
Nurses often report communication difficulties in caring for people with dementia (PWD). Evidence-based interventions to enhance communication are scarce. Therefore, we developed a theory-informed intervention using the Behavior Change Wheel with the aim to improve communication between nurses and PWD. First, ideal communication was defined (targeted behavior) based on the scientific literature, policy reports and consultations of experts (n=7). Second, a focus group meeting with relevant stakeholders (n=7) was organized and observations of nurses (n=9) and PWD (n=9) during daily nursing care were conducted to understand their current behavior and to identify facilitators and barriers for the targeted behavior. Reviewing the literature and consulting experts have shown that ideal communication has to be person-centered and therefore should be tailored to the needs and capacities of PWD. Furthermore, next to verbal communication, attention should be paid to non-verbal communication, including the use of pictograms, objects, and touch. Additionally, the environment has to be recognizable and comprehendible for PWD. However, the focus group meeting and observations have shown that current behavior of nurses is often characterized by a task-oriented instead of person-centered approach. Furthermore, non-verbal communication (e.g., eye contact) is insufficiently used. Identified facilitators and barriers for the ideal communication relate to nurses’ characteristics (e.g., knowledge, awareness, and skills), social influences, and other environmental factors (e.g., resources). These insights were used to develop a theory-informed intervention in close collaboration with relevant stakeholders (e.g., nurses, speech therapists, and policy makers). The systematic development of the intervention and its final version will be presented.